Transfer of an induced preferred retinal locus of fixation to everyday life visual tasks - Barraza-Bernal, Maria J.; Rifai, Katharina; Wahl, Siegfried (Journal of vision (Charlottesville, Va.), 2017)
Subjects develop a preferred retinal locus of fixation (PRL) under simulation of central scotoma. If systematic relocations are applied to the stimulus position, PRLs manifest at a location in favor of the stimulus relocation. The present study investigates whether the induced PRL is transferred to important visual tasks in daily life, namely pursuit eye movements, signage reading, and text reading. Fifteen subjects with normal sight participated in the study. To develop a PRL, all subjects underwent a scotoma simulation in a prior study, where five subjects were trained to develop the PRL in the left hemifield, five different subjects on the right hemifield, and the remaining five subjects could naturally chose the PRL location. The position of this PRL was used as baseline. Under central scotoma simulation, subjects performed a pursuit task, a signage reading task, and a reading-text task. In addition, retention of the behavior was also studied. Results showed that the PRL position was transferred to the pursuit task and that the vertical location of the PRL was maintained on the text reading task. However, when reading signage, a function-driven change in PRL location was observed. In addition, retention of the PRL position was observed over weeks and months. These results indicate that PRL positions can be induced and may further transferred to everyday life visual tasks, without hindering function-driven changes in PRL position.